miR-455-3p ameliorates pancreatic acinar cell injury by targeting Slc2a1 - Zhan, Yinchu; Chen, Chenlin; Wu, Zhiqiang; Zhou, Feng; Yu, Xinping (PeerJ, 2023)
Objective With the number of patients with acute pancreatitis (AP) increasing year by year, it is pressing to explore new key genes and markers for the treatment of AP. miR-455-3p/solute carrier family 2 member 1 (Slc2a1) obtained through bioinformatics analysis may participate in the progression of AP. Materials and Methods The C57BL/6 mouse model of AP was constructed for subsequent studies. Through bioinformatics analysis, the differentially expressed genes related to AP were screened and hub genes were identified. A caerulein-induced AP animal model was constructed to detect the pathological changes of mouse pancreas by HE staining. The concentrations of amylase and lipase were measured. Primary mouse pancreatic acinar cells were isolated and subjected to microscopy to observe their morphology. The enzymatic activities of trypsin and amylase were detected. The secretion of inflammatory cytokines in mouse were measured with the ELISA kits of TNF-α, IL-6 and IL-1β to determine pancreatic acinar cell damage. A binding site between the Slc2a1 3′ UTR region and the miR-455-3p sequence was verified by dual-luciferase reporter assay. The expression of miR-455-3p was quantified by qRT-PCR, and Slc2a1 were detected by western blot. Results A total of five (Fyn, Gadd45a, Sdc1, Slc2a1, and Src) were identified by bioinformatics analysis, and miR-455-3p/Slc2a1 were further studied. HE staining results showed that the AP models were successfully established by caerulein induction. In mice with AP, the expression of miR-455-3p was reduced, while that of Slc2a1 was increased. In the caerulein-induced cell model, the expression of Slc2a1 was significantly reduced after intervention of miR-455-3p mimics, whereas increased after miR-455-3p inhibitor treatment. miR-455-3p decreased the secretion of inflammatory cytokines in the cell supernatant, reduced the activity of trypsin and amylase, and alleviated the cell damage induced by caerulein. In addition, Slc2a1 3’UTR region was bound by miR-455-3p, and its protein expression was also regulated. Conclusion miR-455-3p alleviated caerulein-induced mouse pancreatic acinar cell damage by regulating the expression of Slc2a1.
Keywords: Acute pancreatitis; miR-455-3p; Slc2a1; Mouse pancreatic acinar cells; Bioinformatics analysis